KazakhTTS: An Open-Source Kazakh Text-to-Speech Synthesis Dataset - Saida Mussakhojayeva; Aigerim Janaliyeva; Almas Mirzakhmetov; Yerbolat Khassanov; Hüseyin Atakan Varol (ISCA, 2021)
This paper introduces a high-quality open-source speech synthesis dataset for Kazakh, a low-resource language spoken by over 13 million people worldwide. " "The dataset consists of about 93 hours of transcribed audio recordings spoken by two professional speakers (female and male). It is the first publicly available large-scale dataset developed to promote Kazakh text-to-speech (TTS) applications in both academia and industry. " "In this paper, we share our experience by describing the dataset development procedures and faced challenges, and discuss important future directions. " "To demonstrate the reliability of our dataset, we built baseline end-to-end TTS models and evaluated them using the subjective mean opinion score (MOS) measure. " "Evaluation results show that the best TTS models trained on our dataset achieve MOS above 4 for both speakers, which makes them applicable for practical use. " "The dataset, training recipe, and pretrained TTS models are freely available.
Keywords: Computer science; Speech synthesis; Kazakh; Baseline (sea); Mean opinion score; Reliability (semiconductor); Natural language processing; Speech recognition; Artificial intelligence; Measure (data warehouse); Quality (philosophy); Open source; Metric (unit); Data mining; Software; Linguistics; Engineering; Philosophy; Oceanography; Operations management; Power (physics); Physics; Quantum mechanics; Geology; Epistemology; Programming language; type of access: open access